Assessment of Thermal Pain Sensation in Rats and Mice Using the Hargreaves Test - Cheah, Menghon; Fawcett, James; Andrews, Melissa (Bio-protocol, 2017)
The Hargreaves test is specifically designed to assess thermal pain sensation in rodents such as rats and mice. This test has been used in experiments involving pain sensitization or recovery of thermal pain response following neural injury and regeneration. We present here a step-by-step protocol highlighted with important notes to guide first-time users through the learning process. Additionally, we have also included representative data from a rat model of sensory denervation showing how the data can be analysed to obtain meaningful results. We hope that this protocol can also assist potential users in deciding whether the Hargreaves test is a suitable test for their experiment.